As ações extensionistas e suas contribuições na formação do aluno do Instituto Federal de Educação, Ciência e Tecnologia do Ceará sob a perspectiva da responsabilidade social. - Santos, Emanuelle Andrezza Vidal dos (2019)
There is no denying the growth that has been taking place in the discussions about social responsibility, whether in the private or the public environment, since society came to perceive the relevance of discussing topics such as this from this growing debate that permeate the academic environment and with that reflections about university social responsibility arise, this responsibility can be verified in a more concrete way through extension actions, which in the university environment are activities that have a more efficient dialogue with society. It is imperative that the student trained in these educational institutions can obtain a holistic training so that it can contribute to the transformation in the environment in which it is inserted. This qualitative study, with a descriptive approach, has as general objective to analyze how the extensionist practices developed by the teachers and students through the actions of extension of the education axis contribute to the formation of the student of the IFCE from the perspective of social responsibility of this Institute. The theoretical approach is based on the concepts of extension actions, university extension, social responsibility, university social responsibility, as well as general notions about student formation. The methodological procedures will be applied in six stages and the study hopes, as a result, to reach the proposed objective and give greater visibility to the extension actions. The results show that the extensionist actions contribute directly and in a positive way in the formation of the student. Linked to this, it was noted that there must be an interconnection between the extension actions and that it is necessary to encourage more the participation of the servers. It is concluded, therefore, that when students undertake to seek improvements for their professional formation, they find opportunities within the campus for this, thus becoming a differential for the labor market.